KESENIAN SURAK IBRA DI KAMPUNG SINDANGSARI DESA CINUNUK KECAMATAN WANARAJA KABUPATEN GARUT - Dara, Gradesi Widya (SWARA, 2013)
This the is tiled â€œKESENIAN SURAK IBRA DI KAMPUNG SINDANGSARI DESA CINUNUK KECAMATAN WANARAJA KABUPATEN GARUTâ€ This research is descriptive.Aims to provide an overview of the structure and function music of art Surak Ibra. The structure is composed of several parts, that is part of the opening, contents and cover. While the function music of art as a accompaniment of music and the music that comes from human